Find k:

Asked by  | 27th Apr, 2010, 03:23: PM

Expert Answer:

Dear Student,

Let the two zeroes of the given equation be α and .

Now, we know that

α + β= -b/a

=> α + β= -1/6      (since a= 6, b=1 and c=k)

Also,

αβ= c/a

=> αβ= k/6

 

Now,

(α+β)2= α2 + β2 + 2αβ

=> (-1/6)2= 25/36 + 2k/6            (Since sum of squares of zeroes is given to be 25/36)

=> 1/36 = 25/36 + 12k/36

=> 12k = -24

=> k = -2

 

Hence, k = -2.

 

Regards Topperlearning.

Answered by  | 27th Apr, 2010, 09:26: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.